English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-09-12 11:06:15 · 20 answers · asked by Anonymous in Science & Mathematics Mathematics

20 answers

Well Mr Simon Jones. many people answered your question and some of them are correct. But i have my own reason to answer your question.Can you guess what my reason is ??? just think about it.
but now am ganna answer your question.
x-1/2+x+2/3=x+1/6
x + x - x = 1/6 - 2/3 + 1/2
x = 0

Its your correct answer.

Good Luck

2006-09-12 12:56:54 · answer #1 · answered by sweetie 5 · 0 0

easy bro, the answer is 0 but this is how you do it:

make 1/2 and 2/3 and 1/6 all common, so:

1/2 = 3/6
2/3 = 4/6
1/6 = stays the same

So the equation now is:

x - 3/6 + x + 4/6 = x + 1/6

1) Subtract 1 x from both sides to give

x - 3/6 + 4/6 = 1/6

2) Add -3/6 and 4/6 on the left hand side

x + 1/6 = 1/6

3) Move the 1/6 from the lefthand side over to the right hand side, remember when you move things over like this the sign changes, i.e. positive value becomes negative and vice versa, so:

x = 1/6 - 1/6 which means that x = 0

2006-09-13 04:10:38 · answer #2 · answered by MoJo JoJo 1 · 0 1

this is simple math:

1st group all the x's on one side and the fractions on the other. A point to note is that the sign in front of the fraction or letter changes if moved over to either side, for example, the x on the rhs (right-hand-side) of the equation if moved to the lhs (left-hand-side) will become negative i.e. have a minus sign in front of it.

that means you will have on the lhs:

x - 1/2 + x + 2/3 - x = 1/6

then grouping the x's simplifies the equation to:

x - 1/2 + 2/3 = 1/6

then taking the lhs fractions to the rhs (and abiding by the sign changes involved), you have:

x = 1/2 - 2/3 +1/6

now all thats left to do is simplify the lhs of the equation. By knowing common multiples, you will realise that the common multiple of the three denominators (bottom numbers of a given fraction) is 6.

2 goes into 6 three times therefore multipy top and bottom of first fraction by 3 to get 3/6

3 goes into 6 two times therefore multiply top and bottom of second fraction by 2 to get 4/6

the third fraction already has a denominator of 6 therefore can be left as is.

the equation now becomes:

x = 3/6 - 4/6 + 1/6

seen as the denominators on the rhs are the same you just add or subtract the numerators ( top numbers of the fractions) as required. this leads to the solution of:

x = 4/6 - 4/6 = 0

therefore the value of x is zero.

2006-09-12 12:06:51 · answer #3 · answered by sims 1 · 0 1

easily done...

collect the x terms on side of the equation and the constants on the other side of the equation

eg. x -1/2 + x + 2/3 = x + 1/6

2x +1/6 = x + 1/6

2x - x = 1/6 - 1/6

x = 0


Voila....

2006-09-12 11:09:54 · answer #4 · answered by Mark B 2 · 1 0

x-1/2+x+2/3=x+1/6
x + x - x = 1/6 + 1/2 - 2/3
x = 1/6 + 3/6 - 4/6
x = 0

2006-09-16 06:35:37 · answer #5 · answered by Kemmy 6 · 0 0

I guess it's the fractions causing you a problem.
Try this:
x -3/6 + x + 4/6 = x + 1/6
2x + 1/6 = x + 1/6
2x - x = 1/6 - 1/6
x = 0

2006-09-12 11:13:17 · answer #6 · answered by astephens29 3 · 0 0

Add the like terms and rearrange, to isolate x:

2x -1/2 + 2/3 =x+1/6
x - 1/2 + 2/3 =1/6
x=1/6+1/2-2/3

Find the least common denominator for the fractions, and convert them so they can be added...

x=1/6+3/6-4/6
x=4/6 - 4/6
x=0
That's how you do it!

Now, do the arithmetic...

2006-09-12 11:11:19 · answer #7 · answered by Jack 5 · 0 0

x = 0

2006-09-12 18:00:39 · answer #8 · answered by confused 2 · 0 0

(x-1)/2+(x+2)/3= (x+1)/6 Multiply both sides by 6

3x-3+2x+4= x+1 Combine like terms

5x+1 = x+1 subtract x & 1 from both sides

4x= 0 Multiply both sides by 1/4

x= 0

2006-09-12 11:20:57 · answer #9 · answered by Anonymous · 0 0

x+x-x=1/6+1/2-2/3
x=1/6+3/6-4/6
x=0

2006-09-12 11:09:50 · answer #10 · answered by Anonymous · 0 0

fedest.com, questions and answers